Prospect of Ru(edta) complexes in nitrogen cycle electrocatalysis: a mini review - Chatterjee, Debabrata; Impert, Olga; van Eldik, Rudi (Inorganic Chemistry Frontiers, 2023)
The nitrogen cycle is one of the most important biogeochemical cycles on Earth. This cycle mainly involves redox conversion of dinitrogen when it is converted into ammonia (nitrogen fixation pathway) and the cycle is completed with the conversion of ammonia to dinitrogen (involving nitrification and denitrification pathways). The application of Ru(edta) complexes (edta(4-) = ethylenediaminetetraacetate) in nitrogen cycle-related electrochemical transformation reactions has not been systematically reviewed to date. This review aims to report the research progression on the use of Ru(edta) complexes in catalyzing N-cycle electrochemical transformations. In this review, the role of Ru(edta) complexes in mediating electrochemical reactions pertaining to nitrogen fixation and denitrification in the nitrogen cycle has been discussed, providing in-depth mechanistic knowledge for understanding the varied roles of Ru(edta) complexes pertaining to the many N-cycle-related electrochemical transformations.
CRIS-Team WoS Importer:2023-04-07